Cardiovascular Disease Management and Prevention in Saudi Arabia: Strategies, Risk Factors, and Targeted Interventions - Aseel Awad Alsaidan (International Journal of Clinical Practice)
Cardiovascular diseases (CVDs) remain the main cause of mortality and are generally among the leading causes of morbidity worldwide, thus placing an immense burden on health care. They include coronary artery disease, heart failure, hypertensive heart disease, and stroke. Among these, common risk factors include hypertension, high cholesterol, diabetes, smoking, obesity, and sedentary lifestyle. Yet, with advancements in medical science and pharmacology, these entities remain major challenges to public health worldwide. In Saudi Arabia, the rise in CVDs has been intensified by rapid urbanization and lifestyle changes and needs unique and tailored public health strategies. This review provides a comprehensive overview of the current situation with regard to cardiovascular health in Saudi Arabia, underlining the need for studying CVDs within the local context. It reviews the epidemiology of CVDs in the Kingdom of Saudi Arabia, outlining some of the major risk factors and also their impact on public health. This study also deals with the pharmacological approaches toward cardiovascular health by offering data from clinical trials so far completed, to point out effective strategies of treatment. The overview of prevention methods also includes public health initiatives, lifestyle programs, patient education, healthcare policies, the role of government initiatives, insurance coverage, and international collaborations. The review also elucidates the problems and barriers of the Saudi healthcare system, especially vis-à-vis the primary healthcare setting. In light of improving its healthcare sector, Saudi Arabia has embarked on several reforms within the Universal Health Coverage development initiative set in the framework of Vision 2030.